Hydrogen sulfide‐loaded microbubbles combined with ultrasound mediate thrombolysis and simultaneously mitigate ischemia‐reperfusion injury in a rat hindlimb model - Zhong, Jiayuan; Sun, Yili; Han, Yuan; Chen, Xiaoqiang; Li, Hairui; Ma, Yusheng; Lai, Yanxian; Wei, Guoquan; He, Xiang; Li, Mengsha; Liao, Wangjun; Liao, Yulin; et al. (Journal of thrombosis and haemostasis, 2021)
Background Thromboembolism and subsequent ischemia/reperfusion injury (IRI) remain major clinical challenges. Objectives To investigate whether hydrogen sulfide (H2S)‐loaded microbubbles (hs‐Mbs) combined with ultrasound (US) radiation (hs‐Mbs+US) dissolve thrombi and simultaneously alleviate tissue IRI through local H2S release. Methods hs‐Mbs were manufactured and US‐triggered H2S release was recorded. White and red thromboembolisms were established ex vivo and in rats left iliac artery. All subjects randomly received control, US, Mbs+US, or hs‐Mbs+US treatment for 30 minutes. Results H2S was released from hs‐Mbs+US both ex vivo and in vivo. Compared with control and US, hs‐Mbs+US and Mbs+US showed comparable substantial decreases in thrombotic area, clot mass, and flow velocity increases for both ex vivo macrothrombi. In vivo, hs‐Mbs+US and Mbs+US caused similarly increased recanalization rates, blood flow velocities, and hindlimb perfusion for both thrombi compared with the other treatments, with no obvious influence on hemodynamics, respiration, and macrophage vitality. More importantly, hs‐Mbs+US substantially alleviated skeletal muscle IRI by reducing reactive oxygen species, cellular apoptosis, and proapoptotic Bax, caspase‐3, and caspase‐9 and increasing antiapoptotic Bcl‐2 compared with other treatments. In vitro, hypoxia/reoxygenation‐predisposed skeletal muscle cells and endothelial cells treated with normal saline solution exhibited similar trends, which were largely reversed by an H2S scavenger or an inhibitor of Akt phosphorylation. Conclusion hs‐Mbs+US effectively dissolved both white and red macrothrombi and simultaneously alleviated skeletal muscle IRI through the US‐triggered, organ‐specific release of H2S. This integrated therapeutic strategy holds promise for treating thromboembolic diseases and subsequent IRI.